Personality Assessment of Officer Cadre of Indian Armed Forces: A De Novo Approach - Mishra, Nishi; Ghanekar, Apoorva; Gupta, Arunima (Defence Life Science Journal, 2017)
The present selection system of the officer cadre of the Armed Forces has stood the test of time. However, owing to the transformations and developments in the society, a need was felt to upgrade this system. After a number of interactions and deliberations, a new programme called ‘De Novo system for the Selection of Personnel in the Armed forces’ was initiated. To identify the domains that need to be assessed through this system, job analysis was carried out. Data were collected from the presently employed officers of the Armed Forces, and the officers were asked to fill out survey performa, critical incidents record, task inventory and attribute questionnaire. Job analysis identified 5 domains of assessment, namely, cognition, affect, behaviour, psychomotor, and values. 16 Attributes of military leaders under these 5 domains were also identified. Tests were developed under the three techniques (psychological, group testing, and interview) to assess these 16 attributes and the 5 domains. The prototype of the tests was developed following an assessment centre approach and the trials for the same are due in the coming months.